伴超高水平血清游离轻链的轻链型淀粉样变患者临床特征和预后分析 (Zhonghua Xue Ye Xue Za Zhi, 2021)
OBJECTIVE: To investigate the clinical features and outcomes of patients with lightchain（AL）amyloidosis with an ultra-high level of serum free light-chain（FLC）. METHODS: Five hundred and ninety-five patients with AL amyloidosis were retrospectively reviewed between January 2009 and January 2020 at Peking Union Medical College Hospital. We analyzed the clinical features and prognosis of patients with ultra-high FLC levels［difference between involved and uninvolved light chains（dFLC）>500 mg/L; n＝124］ and those without ultra-high FLC levels（dFLC≤500 mg/L; n＝471）. RESULTS: Patients with ultra-high FLC presented with more frequent cardiac involvement（82.3％ vs 70.1％, P＝0.007）, and a higher percentage of patients with 2004 Mayo Ⅲ stage（41.8％ vs 33.8％, P＝0.029）, but less frequent renal involvement than patients without an ultra-high FLC（59.7％ vs 71.8％, P＝0.009）. Patients with an ultra-high FLC achieved a lower proportion of hematologic（72.4％ vs 82.3％, P＝0.048）and cardiac response（37.3％ vs 54.7％, P＝0.016）and had shorter overall survival（13.0 months vs not reached, P<0.001）and a higher early death rate within 3 months（28.2％ vs 11.3％, P<0.001）than those without an ultra-high FLC. Ultra-high FLC independently predicted worse prognosis in patients with AL amyloidosis（HR＝2.279, 95％CI 1.685–3.083, P<0.001）. CONCLUSION: Patients with an initially ultrahigh FLC represented a subgroup with more common cardiac involvement, more advanced cardiac stages, and extremely poor prognosis.